2013
DOI: 10.1590/s2317-64312013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Competência glótica na doença pulmonar obstrutiva crônica

Abstract: Purpose: This study correlates the extent of maximum phonation time (MPT) with the volume of air exhaled in the first second pulmonary (FEV 1 ) and compares the MPT emission of /s/, /z/ and s/z ratio in healthy subjects and those with chronic obstructive pulmonary disease (COPD). Methods:We studied 14 normal volunteers (control group), mean age 65 years, and 16 patients with COPD, mean age 68 years. The diagnosis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…24,35 Two other studies reported significantly greater S/Z ratios between asthma and COPD patients and controls. 23,36 This study found a significant difference in airflow based on assumed impaired power source with a small effect size. Regardless of etiology, those with impaired power source had significantly greater flows compared to those without (Table 1).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…24,35 Two other studies reported significantly greater S/Z ratios between asthma and COPD patients and controls. 23,36 This study found a significant difference in airflow based on assumed impaired power source with a small effect size. Regardless of etiology, those with impaired power source had significantly greater flows compared to those without (Table 1).…”
Section: Discussionmentioning
confidence: 63%
“…22 Differences in s/z ratios have been found with impaired power source for voicing. 23 -25 Differences in flow, GFI and s/z ratios have already been demonstrated between diagnoses of UVFP, BVFP, and presbylarynges. 5 Aging changes (primarily bowing) have been observed in the non-paretic vocal fold in some UVFP patients over 60 years of age.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies call the attention to the increasing elevation of obesity predominance on worldwide population, including children, in accordance with what was also confirmed in the present study, highlighting a serious public health issue 9,16 . FVC that is the amount of air that can be expired from the lungs after a maximum inspiration [6][7][8] , has showed itself higher on children with more AC. Nevertheless, studies in adults demonstrate that the fat deposit's location influences the ventilation function alterations, such abnormalities being more common on central obesity, where the accumulation of adipose tissue is located on the waist region and has probably a mechanical effect right through the ribcage and the diaphragm restraining the lung expansion causing the reduction of lung volumes 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The forced vital capacity (FVC) evaluation is very used and its measure determines the amount of air that can be expired from the lungs after a maximum inspiration 6 . Maximum phonation time (MPT) evaluation refers to the maximum time an individual can stand an emission during the same expiration, demonstrating the effectiveness of the respiratory and laryngeal coordination 1,3,[5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…4 This can be used as an assessment and treatment tool to rule out pathology and to monitor the progress during and post treatment of voice disorders. 5 Values below 10 second are considered altered. 6 Low MPD values are related to laryngeal pathology.…”
Section: Introductionmentioning
confidence: 99%